PENERAPAN METODE ACTIVITY BASED COSTING PADA TARIF LAYANAN RADIOLOGI DAN LABORATORIUM TERHADAP PENDAPATAN RUMAH SAKIT PARU PAMEKASAN - -, Sayuri (JURNAL AKUNTANSI DAN INVESTASI, 2016)
The main goal of the hospital is to provide medical services, nursing, and health services. One example of service is a service of radiology and laboratory unit, where revenue from such services obtained from tariff to be paid by the users of the services radiological examinations. Determination of tariff of service radiology and laboratory examination is a very important decision, because it can affect the profitability of hospitals lung. The purpose of this study to determine the tariff determination and the results of Rumah Sakit Paru Pamekasan revenue using activity-based costing method that influenced rates of radiology and laboratory services. This research uses descriptive data of quantitative and secondary data sources, which depict or describe a phenomenon by describing a number of variables relating to the problems examined. Based on the results of research conducted in the hospital lung Pamekasan shows that of the rate calculation radiology services and laboratory using methods (ABC), when compared according to the regulations the Governor of East Java, the method (ABC) provides greater results, due to the charging of overhead each -masing more detailed product using the driver